Complications of Kalazar among Children in Hilla-city (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: This study aimed to detect the types of complications of children suffering from kalazar; also toidentify the reason of these complications.Methodology: A descriptive study carried out from Feb15th to June 15th of the academic year 2017. Thesample consisted (109) children from general maternal and children hospital in Hilla/Babylon. The studydesigned and data was collected using structural questionnaire which was prepared by consulting panelresearch expertise, also by assessment approach and interview was done with parents of children. Thecollected data were analyzed through descriptive statistics by frecuency and percentage.Results: The results of the present study indicated that most of the children age were (13-18) yrs.(40.4%);male gender more involved (67%) and (27%) were from Mesaib city. The education level of parents werewithin secondary school, mothers (52%) fathers (43%). The income of affected children families involvedin the study were (51%) poor, which isn’t enough to maintain healthy well being status and medicalrequirements. Complications revealed that children suffers from bleeding tendancy (13.5%) sever animeawere (20%) hepato spleenomegaly were (14.0%) , finally death occurs because of septicemia (37%).Conclusion: Complications accurs because of poor and inappropriate medical diagnosis, also infectivemedical treatment during hospitalization and lake of medical follow up to children suffering from kalazar bythe health team after hospital discharge.
Keywords: Complications, Kalazar, Children, Hilla-city